Directional Reversal Locomotor Training: Effects on Executive Function and Dynamic Balance in Children Aged 6–7 Years - Abdelrahman Ibrahim (Program Studi Pendidikan Kepelatihan Olahraga, 2026)
Cognitively enhanced physical activity could contribute to improving the executive functions for children. However, the particularity of motor-cognitive adaptations throughout various fields are still not clear. The current study aims at examining the impact of directional reversal locomotor training (DRLT) on executive functions and dynamic balance for the stage of early school children. In a randomized controlled trial, 64 first-grade children (with ages 6–7 years) were distributed to the DRLT group (n = 32) or the group, which takes regular physical education classes (n = 32) for 8 weeks. Executive functions were assessed using HTKS-R test and the dynamic balance was assessed using the Y-Balance Test – Lower Quarter. Results after intervention were analyzed using the Analysis of Covariance (ANCOVA). DRLT program demonstrated a significant improvement in executive functions (p < 0.001; effect size d = 2.04), but no significant effect was observed in dynamic balance (p = 0.864; d = 0.13). The results support the domain-specific nature of motor-cognitive adaptations in school interventions.